Julgransodlingar i Sverige : utbud, efterfrågan och lönsamhet - Paulmann, Linda (SLU/Dept. of Forest Products, 2002)
This thesis is about Christmas tree plantations in Sweden, and if its profitable to produce Christmas trees in Sweden. Sweden has 4,3 million households, 3 million of these households buys Christmas trees. 80 % of these Christmas trees are Norway Spruce (Picea abies), which is the most common Spruce in Sweden. Every year over 170 000 Christmas trees are imported to Sweden. The main import comes from Denmark. The thesis is based on a literature survey, a case survey and two questionnaires. The first questionnaire was send to 46 Christmas tree suppliers in southern Sweden. The second questionnaire was send to 77 forest owners in the same area were the Christmas tree suppliers plantations was located. The reason why I made two questionnaires was because it would be interesting to see the differences between how the two groups of landowners use their estate. The first questionnaire showed that the Christmas tree suppliers were not satisfied with the plant material. They also wanted courses and literature about how to produce Christmas trees. The Christmas tree suppliers claimed that it was very profitable to produce Christmas trees, but they had to put a lot of work into it. The questionnaire to the forest owners showed that there wasn't such a big interest to produce Christmas trees. Many of the forest owners believed that it wasn't so profitable to produce Christmas trees, they also thought that it was too much work. The case survey contained two calculations, one over a plantation with Picea abies and the other one over a plantation with Abies nordmanniana. The calculations were based on material from a real Christmas tree plantation in southern Sweden. Both calculations showed that it is very profitable to produce Christmas trees, depending on how good you manage your Christmas tree plantation.